2014
DOI: 10.1182/blood-2013-10-532531
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of acute myeloid leukemia by haploidentical natural killer cells is improved using IL-2 diphtheria toxin fusion protein

Abstract: Key Points• Depletion of host regulatory T cells with IL2DT improves efficacy of haploidentical NK cell therapy for refractory acute myeloid leukemia.• Depletion of Treg and persistence of NK cells for $7 days after NK cell adoptive transfer predicts beneficial clinical responses.Haploidentical natural killer (NK) cell infusions can induce remissions in some patients with acute myeloid leukemia (AML) but regulatory T-cell (Treg) suppression may reduce efficacy. We treated 57 refractory AML patients with lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
337
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 362 publications
(346 citation statements)
references
References 35 publications
(33 reference statements)
7
337
0
2
Order By: Relevance
“…18,42 In several trials testing efficacy of haploidentical NK cells in patients with advanced relapsed or refractory tumors, responses were observed only in a small subgroup of patients and were hampered by co-expansion of Tregs which were thought to be of patient origin. 43-46 Our results suggest that expansion of Tregs may arise in the tumor microenvironment upon PD-L1 expression, and can even occur by expansion from the very small amount of T cells transferred as part of an adoptive NK cell product. To mitigate such in situ Treg generation, PD-L1 blockade may prevent Tregs induction and improve overall efficacy of adoptive NK cell therapy.…”
Section: Discussionmentioning
confidence: 82%
“…18,42 In several trials testing efficacy of haploidentical NK cells in patients with advanced relapsed or refractory tumors, responses were observed only in a small subgroup of patients and were hampered by co-expansion of Tregs which were thought to be of patient origin. 43-46 Our results suggest that expansion of Tregs may arise in the tumor microenvironment upon PD-L1 expression, and can even occur by expansion from the very small amount of T cells transferred as part of an adoptive NK cell product. To mitigate such in situ Treg generation, PD-L1 blockade may prevent Tregs induction and improve overall efficacy of adoptive NK cell therapy.…”
Section: Discussionmentioning
confidence: 82%
“…11 Bachanova et al conducted an adoptive NK cell infusion clinical trial, which demonstrated that depletion of host regulatory T cells with IL-2 diphtheria toxin fusion protein (IL-2DT) improves the efficacy of haploidentical (HID) NK-cell therapy for patients with refractory AML. 12 Therefore, higher levels of Treg cells in the tumor environment might inhibit the GVL effects of NK cells in vivo as well as other cytotoxic T cells post-transplantation. 13 These data indicated that even though IL-2 could prevent cGVHD, relapse is still an important problem that should be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated with the toxin and NK infusion had higher IL-15 levels and improved efficacy of haploidentical NK cell therapy for AML. 98 Finally, a group from the University of Arkansas reported the use of KIR mismatched haploidentical NK cells in the setting of an autologous HSCT for multiple myeloma. The donors' NK cells persisted transiently after infusion, but five patients still relapsed early, two patients had progressive disease, one patient had stable disease, and two patients subsequently relapsed.…”
Section: Exploiting the Graft-versus-leukemia Effect: Manufacturing Nmentioning
confidence: 99%